The views of trainees on the process of training and its relationship to employee performance and productivity in the petroleum sector in Egypt - Karar, Aya (AUC Knowledge Fountain, 2013)
This study examines the views of trainees on their training and the training process relationship to employees’ performance and productivity in two large institutions in the petroleum public sector in Egypt. It is widely held that the Egyptian public sector needs to increase work-related training to improve long-term economic performance, address the skills gap and improve employee productivity. This research is based on a case study of the petroleum sector in Egypt. Qualitative analysis was conducted to explore the relationship between the training of employees and their needs, performance and productivity. The analysis showed that there is a weak relationship between employees training and their performance and productivity, where training programs do not meet the needs of employees and there are issues of favoritism in selecting staff. The study recommends the right steps and process to develop good and effective training programs that will directly influence overall petroleum sector performance and productivity.